Isotypic crystal structures of 1-benzyl-4-(4-bromophenyl)-2-imino-1,2,5,6,7,8,9,10-octahydrocycloocta[b]pyridine-3-carbonitrile and 1-benzyl-4-(4-fluorophenyl)-2-imino-1,2,5,6,7,8,9,10-octahydrocycloocta[b]pyridine-3-carbonitrile - R. A. Nagalakshmi; J. Suresh; S. Maharani; R. Ranjith Kumar; P. L. Nilantha Lakshman (Acta Crystallographica Section E, 2014)
The molecules of the two isotypic title compounds, C25H24BrN3, (I), and C25H24FN3, (II), comprise a 2-iminopyridine ring fused with a cyclooctane ring. In (I), the cyclooctane ring adopts a twisted chair–chair conformation, while in (II), this ring adopts a twisted boat–chair conformation. The dihedral angles between the planes of the pyridine ring and the bromobenzene and phenyl rings are 80.14 (12) and 71.72 (13)°, respectively, in (I). The equivalent angles in (II) are 75.25 (8) and 68.34 (9)°, respectively. In both crystals, inversion dimers linked by pairs of C—H...N interactions generate R22(14) loops, which are further connected by weak C—H...π interactions, generating (110) sheets.